Pemberdayaan Pemuda Milenial Komunitas Parengu Wunga Melalui Produksi “METETES” Untuk Meningkatkan Produksi Usaha Ayam Buras: Pemberdayaan Pemuda Milenial Komunitas Parengu Wunga Melalui Produksi “METETES” Untuk Meningkatkan Produksi Usaha Ayam Buras - Hambakodu, Marselinus; Saragih, Elsa Christin; Maramba, Rambu Susanti Mila; Hajawa, Arni; Bulu, Eduard Yanto; Kilimandang, Hendrikus (MITRA: Jurnal Pemberdayaan Masyarakat, 2024)
Community service aims to empowerment the millennial youth of the Parengu Wunga Community through the production of “METETES” to increase the production of free-range chicken businesses. This community aid activity was carried out in Wunga Village, Haharu District, East Sumba Regency. Community service used instruction, press conference, dialogue, simulation, and practice. The stages of community service are identification of households that use solar cells and free-range chicken businesses, Metetes prototype design, Metetes feasibility testing, assistance with service activities, and evaluation and monitoring. The outputs of this service are Metetes products, publications in online mass media, and IPR for Metetes products. Based on the results of activity feedback conducted on respondents, 70% of service participants were very satisfied regarding the suitability of the material, suitability of needs, quality of material, material delivery, systematics and flow of material, level of participation, closeness to participants, and quality of Metetes products. In addition, service participants have increased skills in the free-range chicken business and the use of Metetes.